Antioxidants in systems of varying complexity chemical, biochemical, and biological aspects - Shishkina, Ludmila N.; Goloshchapov, Alexander N.; Weisfeld, Larissa I. (Apple Academic Press, 2019)
"This volume, Antioxidants in Systems of Varying Complexity, Chemical, Biochemical, and Biological Aspects, brings together innovative research, new concepts, and novel developments in the study of chemistry and biological activity of antioxidants. It is a collection of chapters on new scientific research and practical applications from chemists at several prestigious scientific institutions. It looks at recent significant research and reports on new methodologies and important applications in the field of chemical kinetics, particularly those searching and researching the mechanism of action of new antioxidants. Highlighting the theoretical foundations and a lot of scientific information on the diversity of antioxidants effects on living systems, this authoritative reference source will be a valuable addition for researchers, and students of chemistry and chemical kinetics. Key features: Presents the latest achievements in the study of chemical and biological activity of antioxidants gained by groups of well-known chemists and biophysicists Looks at the screening of new compounds in order to identify promising hybrid structures and potential bioantioxidants; Presents the results of the study of natural antioxidants and the effect of antioxidants on the plants, based on the computerized method for analysis in order to identify the key regularities of antioxidant activity of plant components; Demonstrates the importance of the studies related to natural antioxidants; Provides new research on a variety of topics in the chemical kinetics of new antioxidants; Offers practical recommendations to prevent pathological conditions for the human body and for improving the quality of life; Looks at important issues in chemical kinetics of antioxidants"--